Post-Traumatic Stress Disorder and Defense Mechanism in A Good Person Movie Directed by Zach Braff - Yahya, Rizqi Nabilla Yusdhodila; Yastanti, Unpris; Adi, Wiruma Titian; Nurmalia, Lia (Wanastra: Jurnal Bahasa dan Sastra, 2025)
Experiencing trauma after a distressing event can lead to post-traumatic stress disorder (PTSD). To protect themselves from fear and anxiety, individuals often employ defense mechanisms. The purpose of this study is to identify PTSD and defense mechanisms in the main character, Allison, in the movie A Good Person, directed by Zach Braff. This study uses a descriptive qualitative method and is based on Rasna Kaur Neelam’s theory, which is rooted in the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Additionally, Sigmund Freud’s theory of defense mechanisms is referenced in this research. The results of this study are as follows: (1) The PTSD type exhibited by the main character is comorbid. There are three symptoms: flashbacks, depression, and oxycodone addiction. (2) The predominant defense mechanism in the movie is denial. (3) Through a perspective analysis, it is evident that Allison's behavior is influenced by her id and ego, with an absence of the superego. This lack of the superego significantly impacts her moral judgment and self-criticism, indicating the influence of her PTSD on her psyche.